Kondisi Lalu Lintas dan Tingkat Pelayanan Jalan Persatuan Raya Kabupaten Sinjai - Muh Sucitra Amansah; Istiawati Darwis; Muhammad Dwiyanto Agung Prakasa (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
Persatuan Raya Road serves as a primary urban corridor in Sinjai Regency, accommodating daily mobility and supporting local socio-economic activities. As activities along the corridor continue to increase, the road is becoming more vulnerable to a decline in performance. This study employed a quantitative descriptive approach based on field survey data. Traffic data were collected through 14-hour traffic counting surveys conducted on both weekdays and weekends, complemented by spot speed surveys during peak hours and geometric inventory of the roadway. Data analysis was conducted based on PKJI 2023 by calculating traffic volume, road capacity, degree of saturation, and average vehicle speed to determine the level of service. The highest traffic volume was recorded at 1,094 pcu/hour on weekdays and 939 pcu/hour on weekends. Road capacity ranged from 3,198.56 pcu/hour to 3,322.53 pcu/hour, while the degree of saturation ranged from 0.28 to 0.33 across all segments. The average vehicle speed ranged from 32 to 38 km/h on weekdays and from 38 to 42 km/h on weekends. These findings indicate that Persatuan Raya Road still operates under stable traffic conditions with a generally acceptable level of service. However, the quality of service has begun to experience pressure due to high roadside friction, particularly from on-street parking and intensive roadside activities. This study provides practical input for roadside activity control and short-term traffic management strategies in urban road corridors of regency-level cities.